The punisher (2016), volume 1 ebook On the road. - Cloonan, Becky (The Punisher (2016), 2016)
Collects The Punisher (2016) #1-6. Frank Castle renews his war on crime! But when a by-the-numbers drug bust takes Frank by surprise, the horrible fallout threatens to send him into the heart of darkness! The Punisher won't make that journey alone, though: A DEA agent is on his tail and attempting to get inside his head. What terrors will she find there, and will she survive the experience? Then, Frank hits the road on the trail of the horrific narcotic EMC! The brutal Condor and the psychopathic Face lie in wait, with an army — and a tank! All Frank has in his corner is a passenger — and she's a little girl?! As the explosive climax approaches, can the Punisher take over a lunatic asylum full of drug-enhanced killers — or will he end up an inmate himself?!